2017
DOI: 10.1017/jfm.2017.847
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-induced vibration of a rotating sphere

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. Vortex-induced vibration (VIV) of a sphere represents one of the most generic fundamental fluid-structure interaction problems. Since vortex-induced vibration can lead to structural failure, numerous studies have focused on understanding the underlying principles of VIV and its suppression. This paper reports on an experimental investigation of the effect of imposed axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The experimental methodologies have been validated in previous related studies (e.g. Nemes et al 2012;Zhao et al 2014a,b;Wong et al 2017;Sareen et al 2018). To provide a brief validation, a study of transverse VIV of a non-rotating cylinder was conducted to compare with previous work by Khalak & Williamson (1997) and Zhao et al (2014b).…”
Section: Experimental Validationmentioning
confidence: 92%
“…The experimental methodologies have been validated in previous related studies (e.g. Nemes et al 2012;Zhao et al 2014a,b;Wong et al 2017;Sareen et al 2018). To provide a brief validation, a study of transverse VIV of a non-rotating cylinder was conducted to compare with previous work by Khalak & Williamson (1997) and Zhao et al (2014b).…”
Section: Experimental Validationmentioning
confidence: 92%
“…In addition, mode II also appears sensitive to disturbances and other factors. For example, the experimental study of Sareen et al (2018a) and the computational study of Rajamuni et al (2018b) found that the mode II response weakens if even weak rotation (in the transverse direction) is imposed on the sphere. In particular, they observed a considerable reduction in the maximum oscillation amplitude and a narrowing of the synchronization regime.…”
Section: Robustness Of Modes I and Iimentioning
confidence: 99%
“…Dowell & Hall 2001;Hou, Wang & Layton 2012) on this topic, to which the reader may be referred. Some recent interesting works on vortex-induced vibrations of an elastically mounted sphere are also mentioned here; these include Behara, Borazjani & Sotiropoulos (2011), Sareen et al (2018), Rajamuni, Thompson & Hourigan (2018).…”
Section: Introductionmentioning
confidence: 99%